Addressing another threat to food safety: conflict - Ortega-Beltran, A.; Bandyopadhyay, R. (Wiley, 2023)
Societal Impact Statement The conflict between Ukraine and Russia will negatively affect not only food security but also food safety. Crops produced in Ukraine and Russia are at little risk of contamination by mycotoxins such as aflatoxin. However, due to the conflict, wheat, maize, sunflower, and other crops that would have been produced in and exported from Ukraine will need to be produced somewhere else. If done in warm production areas, strategies will need to be implemented to prevent mycotoxin contamination, which has negative health, social, and economic impacts.